Vortex-induced vibration of a truss girder with high vertical stabilizers. Issue 4 (March 2019) - Tang, Haojun; Shum, KM; Tao, Qiyu; Jiang, Jinsong
To improve the flutter stability of a long-span suspension bridge with steel truss stiffening girder, two vertical stabilizers of which the total height reaches to approximately 2.9 m were planned to install on the deck. As the optimized girder presents the characteristics of a bluff body more, its vortex-induced vibration needs to be studied in detail. In this article, computational fluid dynamics simulations and wind tunnel tests are carried out. The vortex-shedding performance of the optimized girder is analyzed and the corresponding aerodynamic mechanism is discussed. Then, the static aerodynamic coefficients and the dynamic vortex-induced response of the bridge are tested by sectional models. The results show that the vertical stabilizers could make the incoming flow separate and induce strong vortex-shedding behind them, but this effect is weakened by the chord member on the windward side of the lower stabilizer. As the vortex-shedding performance of the optimized girder is mainly affected by truss members whose position relationships change along the bridge span, the vortex shed from the girder can hardly have a uniform frequency so the possibility of vortex-induced vibration of the bridge is low. The data obtained by wind tunnel tests verify the results by computational fluid dynamics simulations.